Peningkatan Hasil Belajar Materi Bangun Datar Menggunakan Model Problem Based Learning di Kelas V - Fazillah, Oryn; Ningsih, Yarisda (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to improve students' learning outcomes in learning to solve problems using the Problem Based Learning model. This type of research is Classroom Action Research (PTK), with a sample of 23 class V students at SDN 16 Air Tawar Timur. This research was carried out in two cycles, cycle I consisted of 2 meetings, and cycle II consisted of 1 meeting. Each cycle consists of four stages, namely, planning, implementation, observation and reflection. Data was collected through observations, interviews and several instruments. The resulting data was analyzed quantitatively and qualitatively. The results of the study showed an increase in learning outcomes, namely in the first cycle the percentage was 76.3 and in the second cycle with a percentage of 91.73. Research shows that the PBL model can help improve student learning outcomes and foster students' interest in learning more. Based on these results, it can be concluded that the Problem Based Learning (PBL) model can improve student learning outcomes in mathematics learning flat building materials.